Prolonged stage duration during incremental cycle exercise: effects on the lactate threshold and onset of blood lactate accumulation - Bentley, D. J.; McNaughton,L. R.; Batterham, A. M. (European Journal of Applied Physiology, 2001)
The aim of this study was to investigate whether increasing the duration of workloads from 3 min to 8 min during incremental exercise would influence workload (W), oxygen consumption (VO2) and heart rate (HR) at the lactate threshold (LT) and the onset of blood lactate accumulation(OBLA). Two groups of six male cyclists were assigned to a well-trained (WT) and recreational (REC) group on the basis of their performance in a maximal incremental ramp test. Each subject then performed two incremental lactate tests (EXT) consisting of six workloads of either 3 min (EXT3-min) or 8 min (EXT8-min) duration. At the completion of each workload whole capillary blood samples were obtained for the determination of blood lactate (BLa) concentration (mM). Power output (Watts, W), HR and VO2 were averaged in the final minute of each workload as well as in the third minute of the EXT8-min. The workload, HR and at the LT and OBLA were subsequently determined from the data of EXT3-min and EXT8-min. The results demonstrate that workload and VO2, but not HR, at the LT and OBLA were higher in the WT cyclists. At the same time, the workload at the LT obtained from the results of the EXT3-min was significantly (P<0.05) higher then the value obtained in the EXT8-min in the WT subjects but not the REC subjects. However, the workload, VO2 and HR at the OBLA, together with the VO2 and HR at the LT were not significantly different when calculated from data obtained from EXT3-min or EXT8-min. The data obtained in this study suggest that incremental exercise protocols using workloads of duration longer than 3 min have the effect of increasing the workload at the LT in well-trained cyclists. However, the OBLA determined in exercise tests using stage increments of either 3 min or 8 min is similar in cyclists of different training status.